(untitled) (Research, Society and Development, 2021)
Objective: to identify the causes related to diarrhea in preschool children and understand the consequences of the condition in the long term. Method: This is a descriptive study, of the literature review type, carried out in the form of a bibliographic research. Results: the main causes related to diarrhea in preschool-age children are: social conditions, food poisoning and pathogens, lack of basic sanitation, lack of immunization and food allergies and intolerances, and their consequences are related to impairments in physical development and cognitive of the child. Conclusion: the proposed objectives were achieved, as it was possible, through the bibliographical research in question, to point out the causes and possible consequences of acute diarrhea in children. The findings allowed the identification of social conditions, food poisoning and pathogens, lack of basic sanitation, lack of immunization and food allergies and intolerances as the main causes, and with this, the need to encourage prophylactic measures and emphasize the participation of parents is emphasized. and responsible for programs related to the prevention of possible infections, and encouragement of immunization.